Role of Patient Satisfaction in Mediating the Effects of Service Quality and Brand Image on Hospital Selection Decisions - Zia Ade Achmad (Journal of Education and Teaching Learning, 2026)
Hospital selection has become an increasingly important issue as patients consider both healthcare quality and institutional reputation before choosing healthcare providers. This study aimed to examine the effects of service quality and brand image on hospital selection decisions, with patient satisfaction serving as a mediating variable. A quantitative cross-sectional design was employed using data collected from 259 patients who had received outpatient or inpatient services at a Type B regional public hospital in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model demonstrated satisfactory indicator reliability, convergent validity, discriminant validity, and construct reliability. The structural model also showed strong explanatory power. The results indicated that service quality and brand image significantly improved patient satisfaction. Brand image and patient satisfaction significantly influenced hospital selection decisions, whereas the direct effect of service quality on hospital selection decision was not significant. Furthermore, patient satisfaction significantly mediated the relationships between service quality and hospital selection decision as well as between brand image and hospital selection decision. These findings suggested that patient satisfaction represented the primary mechanism through which healthcare quality and institutional reputation influenced patients' hospital selection decisions. The study provides empirical evidence supporting the integration of service quality, brand image, and patient satisfaction in explaining hospital selection decisions within regional public hospitals.